2021
DOI: 10.1136/bmj.n1265
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: Looking back at the experiences of graduates and educators during the interim Foundation Year 1

Abstract: In March 2020, thousands of final year medical students in the UK graduated early to join the medical workforce as “interim Foundation Year 1” (FiY1) doctors. Viktorija Kaminskaite, BMJ Clegg Scholar, spoke to the administrators, educators, and junior doctors involved in this graduating year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…27 Three reflective articles have also noted the positive benefit of FiY1 roles in providing opportunities to put theory into practice, increase clinical experience and improve confidence, though there was no formal measurement of change in confidence outlined. [28][29][30] Though the remaining common FY1 tasks, core skills and competencies did not show a significant increase in self-reported confidence, most showed an overall positive trend. Given the relatively small sample size, a significant increase may be observed in these outcomes in a larger powered study, as noted in the GMC report.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…27 Three reflective articles have also noted the positive benefit of FiY1 roles in providing opportunities to put theory into practice, increase clinical experience and improve confidence, though there was no formal measurement of change in confidence outlined. [28][29][30] Though the remaining common FY1 tasks, core skills and competencies did not show a significant increase in self-reported confidence, most showed an overall positive trend. Given the relatively small sample size, a significant increase may be observed in these outcomes in a larger powered study, as noted in the GMC report.…”
Section: Discussionmentioning
confidence: 91%
“…However, a GMC commissioned study report reviewing the FiY1 post concluded that among its benefits it eased transition to starting FY1 and it increased preparedness to practice, with this finding being sustained 2 months later 27. Three reflective articles have also noted the positive benefit of FiY1 roles in providing opportunities to put theory into practice, increase clinical experience and improve confidence, though there was no formal measurement of change in confidence outlined 28–30…”
Section: Discussionmentioning
confidence: 99%